Current perspectives on the optimal management of infantile hemangioma - Grzesik P; Wu JK (Dove Medical Press, 2017)
Peter Grzesik, June K Wu Department of Surgery, Columbia University College of Physicians and Surgeons, New York, NY, USA Abstract: Infantile hemangiomas (IHs) are the most common benign tumor of infancy. As our understanding of their pathobiology has evolved, treatment has become more focused and tailored to specifically treat IH while minimizing adverse effects. Propranolol has gained FDA approval as the first medical therapy for a traditionally surgical disease. This review provides readers with an overview of IH, treatment modalities, and addresses specific considerations in IH disease management. Keywords: infantile hemangioma, medical treatment indications, propranolol, complications of infantile hemangioma